2016
DOI: 10.1038/srep36853
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inoculation of Escherichia coli causes emergency myelopoiesis in zebrafish larval caudal hematopoietic tissue

Abstract: Emergency granulopoiesis occurs in response to severe microbial infection. However, whether and how other blood components, particularly monocytes/macrophages and their progenitors, including hematopoietic stem/progenitor cells (HSPCs), participate in the process and the underlying molecular mechanisms remain unknown. In this study, we challenged zebrafish larvae via direct injection of Escherichia coli into the bloodstream, which resulted in systemic inoculation with this microbe. The reaction of hematopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
(167 reference statements)
0
16
0
Order By: Relevance
“…The most commonly used injection site in zebrafish eleuthero-embryo is the yolk, consequently intra-yolk microinjections have also been automated [ 17,22 ]. Other routes to deliver compounds directly into larvae are intracardiac microinjections, as performed to evaluate the permeability of the blood-brain barrier by fluorescent compounds [ 23,24 ], and intravenous microinjection to evaluate systemic infection of bacterial strains in the zebrafish [ 25,26 ].…”
Section: Main Text: Introduction Results and Discussion (3538/4500 Wmentioning
confidence: 99%
“…The most commonly used injection site in zebrafish eleuthero-embryo is the yolk, consequently intra-yolk microinjections have also been automated [ 17,22 ]. Other routes to deliver compounds directly into larvae are intracardiac microinjections, as performed to evaluate the permeability of the blood-brain barrier by fluorescent compounds [ 23,24 ], and intravenous microinjection to evaluate systemic infection of bacterial strains in the zebrafish [ 25,26 ].…”
Section: Main Text: Introduction Results and Discussion (3538/4500 Wmentioning
confidence: 99%
“…Zebrafish has already been used for the establishment of study models of bacteria infection and their consequences, such as the model of Salmonella infection [23]; Edwardsiella tarda [24], which is a model of pneumococcal meningitis [25]; Streptococcus agalactiae [26], an animal model for tuberculosis [27]; and Vibrio cholerae [28]. In E. coli, the majority of studies are focused on systemic infection and evaluation of inflammatory response using nonpathogenic strains [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work, Willis et al also demonstrated HSC-driven granulopoĂŻesis in response to Shigella flexneri IC injection in zebrafish larvae [85]. Hematopoietic Stem and Progenitor Cell (HSPC) cell death in the context of uncontrolled bacterial burden, and a strong increase of inflammatory cytokine expression (TNFα, IFN 1–2, and IL1) has also been reported [86]. Altogether, these data have established that bacterial infections can increase hematopoiesis via cytokine signaling.…”
Section: Inflammation and Hematopoietic Stem Cell Differentiationmentioning
confidence: 93%